Early childhood psychological factors and risk for bedwetting at school age in a UK cohort. - Joinson, Carol; Sullivan, Sarah; Gontard, Alexander; Heron, Jon (European Child & Adolescent Psychiatry, 2016)
There is evidence for a link between psychological factors and bedwetting, but the direction of this association is unclear. Using data on 8769 children from the Avon Longitudinal Study of Parents and Children, we examined whether difficult temperament (Toddler Temperament Scale at 24 months; Emotionality Activity Sociability Questionnaire at 38 months) and psychological problems (Revised Rutter Parent Scale for Preschool Children at 42 months) are linked to bedwetting at school age. We examined the association between these risk factors and different patterns of bedwetting from 4 to 9 years using multinomial regression. Difficult temperament and psychological problems in early childhood were associated with increased odds of bedwetting at 4-9 years. The strongest associations were most often found for the pattern of bedwetting that was both frequent (at least twice a week) and persistent (up to age 9) e.g. the temperament traits of 'adaptability' and 'mood' were associated with a 33 % increase (95 % confidence interval = 1.14-1.55) and a 27 % increase (1.10-1.47) respectively in the odds of persistent and frequent bedwetting per one standard deviation increase in risk score. Early behaviour problems (e.g. conduct problems [1.43 (1.25, 1.63)] and hyperactivity [1.29 (1.11, 1.50), p < 0.001]) were also associated with frequent and persistent bedwetting, but there was less evidence that early emotional difficulties were risk factors for bedwetting. Adjustment for confounders did not alter these conclusions. The presence of difficult temperament and behaviour problems in early childhood might help to identify children who will continue to experience bedwetting at school age.